Alpha-D-glucan-based vaccine adjuvants: Current status and future perspectives - Patil, Veerupaxagouda; Hernandez-Franco, Juan F.; HogenEsch, Harm; Renukaradhya, Gourapura J. (Frontiers in Immunology, 2022)
Nanoparticles (NPs) are increasingly used as efficient vaccine antigen-delivery platforms and vaccine adjuvants. Alpha (α)-D-glucans are polysaccharide polymers found in plants, animals, and microbes. Phytoglycogen (PG) is a densely branched dendrimer-like α-D-glucan that forms nanoparticle structures. Two simple chemical modifications of corn-derived PG create positively charged, amphiphilic nanoparticles, known as Nano-11, that stimulate immune responses when used as vaccine adjuvant in a variety of species. Nano-11 is a versatile adjuvant that can be used for alternative routes of vaccination and in combination with other immunostimulatory molecules. This review discusses our current understanding of the mechanism of action of Nano-11 and its future potential applications in animal vaccines.